RECEIPT OF AN INTEGRATED COMPUTERIZED PT. JASA RAHARJA (PERSERO) - Muhammad Ismet Rachman; Irfan, Skom, MMSI Irfan, Skom, MMSI (Jurnal Sistem Informasi, 1999)
PT. JASA RAHARJA (PERSERO) is an enterprise which is engaged in insurancewhich seeks to protect people who are victims of public passenger vehicle accidentsand road traffic. So no one when formed Passenger Vehicle Accident InsuranceCompany General and Motor Vehicles who implement and manage the compulsoryaccident insurance funds, and funding public passenger road traffic accidents in theform of a fund for people who become victims of equipment passenger trafficaccidents, and vehicle road traffic.In connection with the duties that all need to known that. PT. JASA RAHARJA(PERSERO) is very careful in monitoring of the insured, given the need to reduce therisk of error for smooth firm. Then run the companies of the importance andcomputerized system to facilitate their work and the data storage security for theinsured. Because the data that the insured will be insured solely the responsibility ofthe company.